2021
DOI: 10.1177/10668969211039415
|View full text |Cite
|
Sign up to set email alerts
|

A Histopathologic Approach to Uterine Niche: What to Expect and to Report in Hysteroscopy-Resected Isthmocele Specimens

Abstract: As one of the emerging complications of caesarean sections (CSs), pathologists will have an important role in handling samples of uterine niches. An isthmocele is a defect at the site of a previous CS scar resulting in a variety of symptoms and niche-related subfertility. There is a deficiency in the literature of the histopathologic features of hysteroscopy-resected isthmocele ridges. Our aim is to fill this gap to highlight what to expect to see and what important findings to report to guide gynecologists to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…3 A small case series examining the histology of resected scar niche (either hysteroscopically because of secondary fertility or hysterectomy because of abnormal uterine bleeding) found that six of eight of the cases contained endocervical type mucosa. 27 Niche formation may also be related to ischemia as, even after adequate elective repair, at least 5% of women will develop a recurrent niche, suggesting inadequate wound healing as a possible contributor. 3 This theory is further supported by the fact that incidence and severity of cesarean scar niche increase with each subsequent cesarean section.…”
Section: Location Of the Uterine Incision During Cesarean Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 A small case series examining the histology of resected scar niche (either hysteroscopically because of secondary fertility or hysterectomy because of abnormal uterine bleeding) found that six of eight of the cases contained endocervical type mucosa. 27 Niche formation may also be related to ischemia as, even after adequate elective repair, at least 5% of women will develop a recurrent niche, suggesting inadequate wound healing as a possible contributor. 3 This theory is further supported by the fact that incidence and severity of cesarean scar niche increase with each subsequent cesarean section.…”
Section: Location Of the Uterine Incision During Cesarean Sectionmentioning
confidence: 99%
“…It has been hypothesized that a lower incision through cervical tissue leads to the formation of a larger scar niche caused by accumulation of mucus in communicating spaces therefore impairing wound healing 3 . A small case series examining the histology of resected scar niche (either hysteroscopically because of secondary fertility or hysterectomy because of abnormal uterine bleeding) found that six of eight of the cases contained endocervical type mucosa 27 …”
Section: Cause Of Cesarean Scar Niche Formationmentioning
confidence: 99%
“…The recent online publication of the article entitled "A histopathologic approach to uterine niche: What to expect and to report in hysteroscopy-resected isthmocele specimens" in the "International Journal of Surgical Pathology", has shown some absent or scarce histopathologic features in hysteroscopy-resected isthmocele specimens compared to previously reported cases of isthmoceles in hysterectomy specimens. [1][2][3][4][5] We became interested in the histopathologic features in isthmoceles that can be identified in hysterectomy specimens which might have been absent or obscured in hysteroscopy-resected isthmoceles. Our aim this time is to compare and contrast the clinicopathologic features of isthmoceles procured from hysterectomy and isthmoplasty specimens.…”
mentioning
confidence: 99%
“…6 Some of the clinicopathologic differences might indicate two groups of patients with Caesarean section-related isthmoceles depending on their levels, sizes, shapes, contents, and histologic properties of their mucosa, edge wall, surrounding tissue, residual myometrial and scar tissues. 1,6 Some findings may have potential pathologic and clinical implications. For example, the surface epithelial atypia and sloughed degenerate epithelial cells might have interpretation pitfalls when examining cervical smears and biopsies.…”
mentioning
confidence: 99%